Nuclear Reactor Kinetics and Plant Control - Oka, Yoshiaki; Suzuki, Katsuo; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
Understanding time-dependent behaviors of nuclear reactors and the methods of their control is essential to the operation and safety of nuclear power plants. This book provides graduate students, researchers, and engineers in nuclear engineering comprehensive information on both the fundamental theory of nuclear reactor kinetics and control and the state-of-the-art practice in actual plants, as well as the idea of how to bridge the two. The first part focuses on understanding fundamental nuclear kinetics. It introduces delayed neutrons, fission chain reactions, point kinetics theory, reactivity feedbacks, and related measurement techniques. The second part helps readers to grasp the theories and practice of nuclear power plant control. It introduces control theory, nuclear reactor stability, and the operation and control of existing nuclear power plants such as a typical pressurized water reactor, a typical boiling water reactor, the prototype fast breeder reactor Monju, and the high-temperature gas-cooled test reactor (HTTR). Wherever possible, the design and operation data for these plants are provided.
Part I Nuclear Reactor Kinetics -- Delay Neutron and Nuclear Reactor Kinetics -- Point Reactor Kinetics -- Temperature Effect of Reactivity -- Kinetics Parameters and Reactivity Measurement Experiments -- Part II Actual Nuclear Reactor Plant Control -- Control system basics and PID control -- Reactor Stability Study -- Actual Operation Control of Boiling Water Reactor -- Actual operation and control of PWR -- Actual operation and control of fast reactor -- Actual operation and control of high temperature engineering test reactor -- New Control Theory and its Application Answers to practice exercises.
Keywords: Engineering; Electric engineering; Nuclear engineering; Engineering; Nuclear Engineering; Energy Technology